2010
DOI: 10.4103/1319-1683.74325
|View full text |Cite
|
Sign up to set email alerts
|

Physicians′ therapeutic practice and compliance of diabetic patients attending rural primary health care units in Alexandria

Abstract: Objectives:The objectives of the study were to investigate physician’s therapeutic practice and the compliance of diabetic patients attending rural primary health units in Alexandria.Material and Methods:A cross-sectional study was conducted and a multistage stratified random sample method was used for the selection of 600 diabetic patients. Data were collected by means of an interviewing questionnaire, an observation checklist, review of prescriptions and laboratory investigations. A scoring system was made f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 9 publications
8
29
5
1
Order By: Relevance
“…The results of the present study show that, among the participants 26.1% were found to have good adherence, 47.9% had a fair adherence, and 26% had poor adherence. These results are not in agreement with Nahla et al, [10], who reported that about 57% of patients always took their medication as prescribed and on time. In addition, the results by Kravitzetet al, 11 in Scotland found that 91% of the diabetic patients reported that they actually took their medication as prescribed.…”
Section: Discussioncontrasting
confidence: 93%
“…The results of the present study show that, among the participants 26.1% were found to have good adherence, 47.9% had a fair adherence, and 26% had poor adherence. These results are not in agreement with Nahla et al, [10], who reported that about 57% of patients always took their medication as prescribed and on time. In addition, the results by Kravitzetet al, 11 in Scotland found that 91% of the diabetic patients reported that they actually took their medication as prescribed.…”
Section: Discussioncontrasting
confidence: 93%
“…Physical activity was the only behavior that did not show significant improvement. This was in agreement with a previous study conducted in our country and concluded that the exercise regimen showed the lowest values among all studied items of compliance to management (i.e., taking medications as prescribed, taking medication in time, dietary control, and exercise control) (Ibrahim et al 2010). The authors explained this low patient compliance with physical activity as being due to the fear of increased risk of trauma and/or the perception that exercise could exacerbate their illness.…”
Section: Discussionsupporting
confidence: 85%
“…Another study done at a primary care level in Egypt found that compliance of diabetic patients with most types of diabetes regimens was low [15]. There has been a change in dietary patterns and lifestyles of middle eastern people over the past few decades, with increased use of convenience foods and sedentary lifestyles.…”
Section: Discussionmentioning
confidence: 99%